Adoption of AI Driven Ecological Preaching Systems using SEM PLS Analysis - Rusmiati, Elis Teti; Febrina, Laila; Sari, Yunita; Sakti, Essy Malays Sari (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study investigates the factors influencing the acceptance of AI-based ecological preaching and its impact on individuals' intention for ecological awareness. Although AI has been widely applied in various fields, limited studies have examined its role in ecological preaching, indicating a research gap in understanding how technology-driven da’wah shapes environmental awareness. Leveraging a quantitative approach, the research employs structural equation modeling with partial least squares (SEM-PLS) using SmartPLS 4 to analyze data from 147 respondents. The proposed model examines the roles of Clarity of Information (CLR), Relevance (REL), Trust (TRUST), and Technology Suitability (SPFIT) as key determinants of Attitudes towards AI Da'wah (ATT), and subsequently, how these attitudes shape the Intention for Ecological Awareness (INT). Findings indicate that clarity of information, relevance, and trust in the AI system significantly influence attitudes toward AI-based preaching, with technology suitability also playing a crucial role. Furthermore, attitudes towards AI da'wah were found to be a strong predictor of individuals' intention to embrace ecological awareness. The main findings highlight the relevance of this study to sustainable development and digital ethics, offering valuable insights for developers and religious institutions. The results contribute to the growing literature on the intersection of AI, religion, and environmentalism, providing a foundational understanding of user acceptance in this emerging field.